Social Status and Oral Hygiene with Quality of Life in Patients with Primary Hypertension - Masriadi; Muhammad Fajrin Wijaya; Maqh irah Amiruddin; Tuti Alawiyah; Nur Rahmayani (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background:The main problem in primary hypertension is that most people who have been diagnosed with primary hypertension do not know the etiology clearly.To find out the the relation between social status and oral hygiene with quality of life in primary hypertension. Methods:The type of research used was an observational in a cross-sectional study design.The study was conducted in February-May 2021. The number of sampling was 61 people. The sampling method uses purposive sampling technique. The results of data collection were tested by using the Path Analysis test.Results: Research conducted at Padongko Public Health Center in Barru Regency. Based on the results of the analysis of the path analysis of social status tests on primary hypertension, the results obtained p value 0.188> α 0.05, oral hygiene against primary hypertension results obtained p value0.914> α 0.05, this Ha obtained means that there is a the relation but not significant, while social status on quality of life results are obtained p value 0.837> α 0.05, oral hygiene against quality of life results obtained pvalue0.227> α 0.05, this Ha obtained means there is the relation but not significant, while the the relation of primary hypertension to quality of life has a significant the relation where the results of p value 0.012 <α 0.05.Conclusion: There is the relation between social status and oral hygiene with quality of life in patients with primary hypertension but does not appear significantly.